Extracellular vesicles from hypoxia-pretreated adipose-derived stem cells regulate hypoxia/reoxygenation-induced human dermal microvascular endothelial apoptosis and autophagy in vitro. Issue 2 (February 2023) - Yinhua Zhao, M.M.; Yanyu Shi, M.M.; Lin, Huang
Abstract: Recent studies suggest hypoxia can promote adipose-derived stem cells (ADSCs) to attenuate hypoxia/reoxygenation (H/R)-induced damage to human dermal microvascular endothelial cells (HDMECs). Extracellular vesicles (EVs), isolated from ADSCs, play an-important role in the fields of regenerative medicine. Here, we aimed to investigate the effect of EVs isolated from hypoxia-pretreated ADSCs (ADSC-EVs[H]) on HDMECs to attenuate ischemia/reperfusion injury of free skin flaps. First, we characterized EVs isolated from normoxia-cultured ADSCs (ADSC-EVs[N]) and ADSC-EVs(H). Experimental data indicated that EVs isolated from ADSCs consisted of lipid-bilayer vesicles that exhibited positive expression of vascular endothelial growth factor (VEGF) and marker proteins CD9, CD63 and CD81, and the mean particle size of EVs in the hypoxia-pretreated ADSCs (ADSC[H]) group was smaller (74.17 nm) than in the normoxic-cultured ADSCs (ADSC[N]) group (93.87 nm). Hypoxic pretreatment increased the number of EVs. Later, we favorably constructed the co-culture model of EVs isolated from ADSCs (ADSC-EVs) and H/R-induced HDMECs. Cell counting kit-8, Ethynyldeoxyuridine assay, western blotting and immunofluorescence staining showed that ADSC-EVs(H) promoted the survival of HDMECs and increased LC3 level. Apoptosis, reactive oxygen species (ROS) and JC-1 mitochondrial membrane potential (MMP) assays revealed that ADSC-EVs(H) reduced the apoptosis rate and ROS accumulation and increased MMP level in HDMECs, indicating that ADSC-EVs(H) effectively attenuated H/R-induced damage in HDMECs through autophagy activation and the-inhibition of apoptosis and oxidative stress. This study confirmed that ADSC-EVs(H) could effectively regulate the proliferation, apoptosis, oxidative stress, and autophagy expression of H/R-induced HDMECs in vitro, and therefore the transplantation of ADSC-EVs(H) may provide novel insights for the transplantation of free skin flaps.